The complex epidemiology of extended-spectrum β-lactamase-producing Enterobacteriaceae. (May 2015) - Tal Jasper, Ruthy; Coyle, Joseph R; Katz, David E; Marchaim, Dror
ABSTRACT : Antimicrobial resistance is a growing worldwide iatrogenic complication of modern medical care. Extended-spectrum β-lactamases have emerged as one of the most successful resistance mechanisms, limiting our therapeutic options to treat various human infections. The dissemination of these enzymes to the community probably signifies an irreversible step. This paper will review the evolution of human infections associated with extended-spectrum β-lactamase-producing organisms in the past 20 years, and will present and discuss the current challenges, controversies, debates and knowledge gaps in this research field.